Freemasonry and socialism: the dispute for educational reform in Saltillo, 1933-1937 - Díaz Martínez, Leonardo Emmanuel (2021)
This article examines the actions taken by some freemasons that began in the lodge "Fraternidad N ° 20", in the city of Saltillo, Mexico. These were set off by the socialist educational reform of 1934 promoted by President Lázaro Cárdenas. During his government, the socialist educational reform implemented changes to article 3 of the 1917 Constitution of Mexico, which put primary education under State control. This brought up differences with the conservative sectors (parents and Catholic Church) thus generating a political-social ideology dispute.